Exploring Pre-service Science Teachers’ Perspectives on the Nature of Science: A Comparative Study Between China and Canada - Zhang (张桂花), Guihua; Li (李远蓉), Yuanrong; Zhou (周国强), George; Ho, Sonia Wai-Ying (ECNU Review of Education, 2022)
The Nature of Science (NOS) is an important component of scientific literacy. Science teachers’ Views of the Nature of Science (VNOS) directly affect their teaching behaviors. Therefore, it is of great significance to explore science teachers’ VNOS and find ways of improvement. This study was designed to comparatively investigate preservice science teachers’ VNOS between China and Canada. The study employed a survey design to explore how Chinese and Canadian preservice science teachers understood the seven different aspects of NOS. Data showed that preservice science teachers in China and Canada both hold a modern view about science education. The level of Chinese and Canadian participants’ understanding of NOS was above the relatively naive level. Chinese teachers had better macro-understanding toward science education, but their micro-mastery was insufficient. The Canadian participants had a better understanding of the NOS than their Chinese counterparts. The study suggested that there is a need to reconstruct the preservice science teacher education curriculum in China and promote the transformation in the science teacher educational system.